Bioadhesive properties of β-limit dextrin - XIN QI; Richard F Tester (Frontiers Media S.A., 2011)
Purpose. β-Limit dextrin has been studied for many years as a means to investigate the internal structures of amylose and amylopectin. However its role as an excipient in the pharmaceutical industry has never been reported. This paper is the first one in a series to explore its potential use as an excipient to aid drug delivery. Methods. The bioadhesive properties of β-limit dextrin were studied using a texture analyser and compared with two well-known bioadhesive polymers - carbopol and chitosan (as controls). Results. The β-limit dextrin has significant mucoadhesive properties; similar to carbopol but superior to chitosan. Conclusions. The nature of β-limit dextrin (a starch derivative) makes it safe to consume and provides a natural alternative when compared with synthetic polymers. In addition, the polysaccharide can be digested by salivary amylase and thus provide a clean mouth feel.